(untitled) (Journal of Forensic Medicine & Toxicology, 2012)
Introduction: Road traffic accident related deaths contributed 25 to 35% of all autopsies between 2003 and 2006 at the National Institute of Forensic Medicine (NIFM), Hospital Kuala Lumpur. The causes of death were usually head injury, chest injury, abdominal and multiple injuries. Head injury, by far, was the most common cause of death recorded by the Institute. The objectives of the study were to determine: (a) the demographic characteristics of fatal motor vehicle accident (MVA) victims; (b) category of road users involved in such events; and (c) the causes of death, types of brain damage as well as presence of diffuse axonal injury (DAI) in the study subjects.